Relationship between mean platelet volume and vitamin D deficiency in fibromyalgia - Yildirim, Tulay; Solmaz, Dilek; Akgol, Gurkan; Ersoy, Yuksel (Scientific Publishers India, 2016)
Objective: To investigate whether vitamin D deficiency is associated with high mean platelet volume (MPV) in fibromyalgia (FMS) compared to healthy controls. Methods: Ninety-nine patients with fibromyalgia and ninety-nine age-and sex-matched healthy female control subjects were included. Tenderness was evaluated by applying pressure (4 kg/cm(2)) over 18 specific body points, and the number of tender points was recorded. FMS patients completed visual analog scales (VAS) to evaluate their level of pain and were evaluated with the FMS Impact Questionnaire (FIQ) and Beck Depression Inventory (BDI). In all cases, platelet count and MPV were measure as part of each full blood count. Serum 25(OH) D3 levels were analyzed with Enzyme-Linked ImmunoSorbent Assay (ELISA). Patients were divided into three groups as follows: Group 1, vitamin D level of <10 ng/ml (n=33); Group 2, vitamin D level of 10-20 ng/ml (n=3); and Group 3, vitamin D level of > 20 ng/ml (n=33). Results: MPV values were significantly higher in the vitamin group 1 compared to the control group. There was no significant difference between the vitamin group 3 and the controls. A negative correlation was determined between MPV and vitamin D status or 25 (OH) D level. Conclusion: Vitamin D deficiency may contribute to an increase in MPV levels, which is a risk factor in cardiovascular disease (CVD) in FMS.
Keywords: Fibromyalgia; Mean platelet volume; Vitamin D